Pengelolaan pendidikan sekolah dasar di Era Revolusi industri 4.0 - Fitani, Laila Muafatin Minal (Maliki Interdisciplinary Journal, 2024)
As time passes, technology has become the center of many things in the current era, which is known as the fourth industrial revolution or Education 4.0. Education, in particular, has also undergone development. Primary education must have good quality and value. The readiness of educators and school principals is also crucial to answer the challenges of the times. The management strategy is also essential and should always be prepared. Based on these reasons, this study discusses the management of education, especially in primary schools, in the era of the fourth industrial revolution.